Seven secrets of COVID-19: fever, ACE2 receptors, gut-lung axis, metabolomics, microbiomics, probiotics, diet - Vassilios Fanos; Roberta Pintus; Maria Cristina Pintus; Michele Mussap; Maria Antonietta Marcialis (Journal of Pediatric and Neonatal Individualized Medicine, 2021)
The aim of this work is to investigate 7 secrets of COVID-19 (fever, ACE2 receptors, gut-lung axis, metabolomics, microbiomics, probiotics, diet), hoping to reveal a small part of some of these and to increase anyhow the knowledge on SARS-CoV-2 and its weaknesses to be able to defeat it.